Building an Ear-EEG System by Hacking a Commercial Neck Speaker and a Commercial EEG Amplifier to Record Brain Activity Beyond the Lab. Issue 1 (16th October 2020) - Bleichner, Martin G.; Emkes, Reiner
Electroencephalography (EEG) allows measuring human brain activity for scientific, diagnostic and therapeutic purposes. For scientific purposes, EEG is traditionally used to study the brain-behaviour relationship under well controlled laboratory conditions while the participant sits quietly in a room. Consequently, our knowledge regarding the brain-behaviour relationship was limited to human behaviour under constrained conditions. The development of mobile EEG hardware in the last years allows moving beyond the lab and studying brain activity in everyday life. Most EEG systems record from electrodes that are distributed over the head, kept in place with an elastic cap or net. For long term EEG recordings, to study natural behaviour in public, these systems are not optimal, as they are rather bulky and unpleasant to wear for longer periods. We argue for "transparent", ear-centered EEG systems instead. Transparent in the sense that both the person wearing the EEG system as well as the people interacting with that person are not disturbed by it. We describe here the integration of a commercially available research-grade mobile EEG amplifier and a commercially available neck speaker as a mounting system to be used in combination with ear electrodes (cEEGrid). This nEEGlace can be used for ear-EEG recordings in public over extended periods of time. The integrated microphone and the integrated speakers provide the possibility to play and record sound. This allows conducting experiments on auditory perception beyond the lab by both studying the brain responses to naturally occurring sounds as well as to experimental auditory stimuli. We describe the general design, present a working prototype, outline a number of use cases and discuss future improvements of the proposed design.